HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN KEBERHASILAN PENYAPIHAN VENTILASI MEKANIK DI RUANG ICU - Rismiati, Rismiati; Endiyono (Jurnal Keperawatan Malang, 2025)
Background: Weaning patients from a ventilator is a complex and challenging task for nurses. This condition requires nurses to understand the criteria for weaning in order to achieve successful outcomes for patients on mechanical ventilation. Knowledge plays an important role in determining the success of mechanical ventilation weaning. Purpose: To determine the relationship between the level of nurses' knowledge and the process of weaning from mechanical ventilation in the ICU room Methods: This study is an analytical observational study using a cross-sectional approach. The sample selection used a total sampling of 33 respondents. Data analysis used the chi square test. Result: Most of the respondents were 31-36 years old, 13 (39.4%), male gender, 21 (63.6%), had a bachelor's degree, 23 (69.7%), work experience of 1-5 years and > 11 years, 13 (39.4%) each, and ICU training had been carried out by 17 (51.5%). Respondents were mostly knowledgeable as many as 28 respondents (84.8%) and the process of implementing mechanical ventilation weaning in the ICU was appropriate as many as 24 (72.7%). Data analysis showed that there is a relationship between nurses’ knowledge level and the process of weaning from mechanical ventilation, with p = 0.004 (< 0.05). Implication: Hospitals need to hold routine training and continuing education programs related to mechanical ventilation, including effective weaning techniques, to improve nurse competence.